Fractional crystallization for wastewater treatment from food industries: effect of operation temperature and solution flowrate: article / Siti Nurajjar Jami and Farah Hanim Ab. Hamid - Jami, Siti Nurajjar; Ab. Hamid, Farah Hanim (2018)
In food industry, one of the problems constituent to it is the production of wastewater as by-product, in which this problem contributed to the severeness of the environmental quality, specifically water pollution, as well as to the human health. It is a challenge for researchers around the world to develop effective technology to address this problem. Crystallization technique is seen as one of the potential techniques to deal with this issue. In this work, progressive freeze crystallization (PFC) technique was studied for its effectiveness in wastewater treatment for food industry. In this process, a single layer of ice crystal formed on the surface of the crystallization vessel, making it easier to separate ice crystal from the concentrated solution. The effects of operation temperature and solution flowrate to the effective partition constant, K and solute recovery, Y were investigated to indicate the efficiency of the PFC process on glucose solution as the modeled wastewater sample. It was discovered that lower operation temperature and higher solution flowrate causes K value to decrease while Y value increased, indicating higher efficiency. The highest efficiency was found at the operation temperature of-10 o C with K and Y values of 0.4902 and 1.0048 respectively and at solution flowrate of 500 rpm, where Kand Yvalues were 0.6521 and 0.9041.